A Secondary Student’s Problem Solving Ability in Learning Based on Realistic Mathematics with Ethnomathematics - Nursyahidah, Farida; Saputro, Bagus Ardi; Rubowo, Maya Rini (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2018)
The aim of this research is to describe profile of problem solving ability of secondary students with high mathematical ability in learning based on realistic mathematics supported by ethnomathematics. This study is descriptive qualitative reasearch. The method of data collection used in this study are written test and interview. Subject of this study is secondary students on class VIIIA SMPN 37 Semarang. The data analysed in this study is problem solving ability which is suitable to problem solving ability of Polya and result of an interview to research subject. The result of this study is profile of problem solving ability of the high mathematical ability student is very good. The student problem solving ability starting from understanding the problem completely and make good planning to solve the problem, then he can do the correct process and produce the right answer. In addition, he could look back the process but still uncomplete yet. Furthermore, hopefully this result will help the teacher in choosing the appropriate strategy or instructional approach in order to improve the students problem solving ability.